2017
DOI: 10.1016/j.parepi.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminth infections of dog in Enugu State, South Eastern Nigeria

Abstract: The prevalence of gastrointestinal helminth infections of dog in Enugu State, South Eastern Nigeria was studied retrospectively and prospectively. In the retrospective study, records of all diagnosed helminth infections of dogs brought to the University of Nigeria Veterinary Teaching Hospital, Nsukka from January, 2006 to September 2013 were collated and analyzed. The prospective study was carried out between October 2013 and July 2014 by examination of 263 faecal samples collected per rectum from dogs present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
24
5
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 19 publications
11
24
5
8
Order By: Relevance
“…Contrary to the finding of this study, sex of host animals had been reported to significantly influenced prevalence of gastrointestinal parasites [24], In few studies, female dogs are likely to contract intestinal parasites than male dogs [23,26], This had been linked to the physiological peculiarities of female dogs that constitute stress factors and thus reduce their immunity to infections [24], Commonly, feed brands are risk factor reported to be associated with occurrence of gastrointestinal parasites in dogs [20]. In this study, no association of gastrointestinal parasites with feed brands has been established.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the finding of this study, sex of host animals had been reported to significantly influenced prevalence of gastrointestinal parasites [24], In few studies, female dogs are likely to contract intestinal parasites than male dogs [23,26], This had been linked to the physiological peculiarities of female dogs that constitute stress factors and thus reduce their immunity to infections [24], Commonly, feed brands are risk factor reported to be associated with occurrence of gastrointestinal parasites in dogs [20]. In this study, no association of gastrointestinal parasites with feed brands has been established.…”
Section: Discussioncontrasting
confidence: 99%
“…In Nigeria, only a few studies on the assessment of gastrointestinal parasites among exotic kenneled dogs have been carried out [23,24], Commonly, these base line data revealed low prevalence such as 12.3% in Ibadan [25], in Jos 7.68% [23], and 11.4% in Enugu [26], Conversely, these researches were conducted among local dogs and comparatively few samples of exotic dogs which might have influenced the statistical power of the analysis. In most of the studies, a wide variation in prevalence of gastrointestinal parasites exists among the local dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, this study found that dog's age is significantly associated with the prevalence of helminthiases [16,17,18]. In addition, it is consistent with the research by Neves et al [18] and Idika et al [23] who found that dog's sex and breed did not statistically influence the prevalence of helminthiases. Furthermore, Awadallah and Salem [24] and Abere et al [14] found that feeding practices did not impact on the prevalence of canine helminthiases in Egypt and Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…The study was conducted on stray dogs at chagni town using cross-sectional study design. Sample size was determined based on studies conducted previously (Amissah-Reynolds et al, 2016;Idika et al, 2017;Kiflu et al, 2016;Israel, 1992). Fecal sample collection and questionnaire were the methods used.…”
Section: Study Animals and Study Designmentioning
confidence: 99%